Challenges in insulin initiation among Hispanics/Latinos with diabetes in the United States. Issue 5 (October 2020) - Kaushik, Puneet; Reed, Beverly; Kalirai, Samaneh; Perez-Nieves, Magaly
Highlights: Disparities exist regarding insulin initiation in Hispanics/Latinos in the U.S. Barriers to insulin initiation in Hispanic/Latino diabetes patients were identified. Socioeconomic and sociocultural factors were commonly reported barriers. Tailored strategies are required to improve long-term health outcomes. Abstract: Purpose: The prevalence of diagnosed diabetes in the United States (U.S.) is particularly high among people of Hispanic/Latino ethnicity, placing this population at risk of developing diabetes-related complications. We conducted a systematic literature review to understand and communicate the current gaps and disparities, including myths and misconceptions, regarding insulin initiation among the Hispanic/Latino population in the U.S. Methods: We searched MEDLINE and MEDLINE In-process, e-pubs ahead of print (OvidSP), EMBASE (OvidSP), and the Cochrane Central Register of Controlled Trials (CENTRAL). The search strategy combined free text and controlled vocabulary terms and was developed to identify challenges associated with insulin use and initiation, as well as myths/misconceptions associated with insulin use. The quality of included studies was assessed using the National Institutes of Health (NIH) quality assessment tool. Principal results: In total, 777 articles were identified, with 13 articles included for data synthesis. Frequently reported barriers to initiating diabetes treatment among the Hispanic/Latino community related to socioeconomic and sociocultural factors. In particular, limited health literacy and access to health care, as well as low education and economic status, were common factors preventing treatment initiation for diabetes. Cultural factors, including language, food preferences, and lack of family support were also evident, with misconceptions and fears concerning insulin being commonly reported. Patients also described barriers concerning health care providers, including interpersonal issues and difficulties with communication and language. Major conclusions: Overall, the current literature highlights many obstacles facing Hispanic/Latino patients in initiating insulin treatment for diabetes. Although limited research was identified, we describe common barriers and themes among this minority population. Awareness of these barriers is important for health care providers, enabling them to identify and address insulin-related fears and misconceptions and to be mindful of their cultural competency. Additionally, knowledge of current barriers will guide further research aimed at developing tailored strategies and tools to improve long-term health outcomes and quality of life in this population.